Peran Polisi Kehutanan dalam Penanggulangan dan Pencegahan Tindak Pidana Illegal Logging - Kahar S. Laiya; Robby W. Amu; Arifin Tumuhulawa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to determine and analyze the role and effectiveness of the forestry police in overcoming illegal logging crimes. The type of research used is empirical juridical, by collecting data based on facts in the field and analyzed qualitatively descriptive. The role of the forestry police includes non-penal and penal efforts. Non-penal efforts are in the form of prevention such as providing appeals for environmental conservation, reforestation, supervision of forest utilization permits, mapping of vulnerable areas, and improving the quality and quantity of personnel. Penal efforts include arresting perpetrators, confiscating evidence, making minutes of examination, and coordinating with other law enforcement officials. Factors affecting the effectiveness of the forestry police include legal substance, legal structure, community culture, facilities and infrastructure, area compared to the number of personnel, population growth, and increasing modus operandi due to high demand for timber. Synchronization of regulations between sectors is needed to avoid overlapping rules. The government also needs to strengthen forestry police infrastructure and encourage active community involvement in preserving forests in North Gorontalo District.